2013
DOI: 10.1111/gcb.12200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid climate driven shifts in wintering distributions of three common waterbird species

Abstract: Climate change is predicted to cause changes in species distributions and several studies report margin range shifts in some species. However, the reported changes rarely concern a species' entire distribution and are not always linked to climate change. Here, we demonstrate strong north-eastwards shifts in the centres of gravity of the entire wintering range of three common waterbird species along the North-West Europe flyway during the past three decades. These shifts correlate with an increase of 3.8 °C in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
225
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(250 citation statements)
references
References 31 publications
(33 reference statements)
16
225
1
3
Order By: Relevance
“…The abundance models suggest that recent climate change has been a significant driver of breeding seabird and wintering waterbird populations in western Europe over the last 30 years, as supported by specific studies of both groups 27,36 . By incorporating data from outside the UK when producing our models, we were able to capture most of the likely future variation in climate at these sites, even under the A1FI 2080 scenario (Supplementary Figure XX), although future climate change may result in increasingly divergent ecological processes to those currently operating in particular locations or climates 39 .…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The abundance models suggest that recent climate change has been a significant driver of breeding seabird and wintering waterbird populations in western Europe over the last 30 years, as supported by specific studies of both groups 27,36 . By incorporating data from outside the UK when producing our models, we were able to capture most of the likely future variation in climate at these sites, even under the A1FI 2080 scenario (Supplementary Figure XX), although future climate change may result in increasingly divergent ecological processes to those currently operating in particular locations or climates 39 .…”
mentioning
confidence: 72%
“…Greater losses are projected at the species-level compared to the combined, multiple species network, where species can gain qualifying status at new sites currently protected for other species (Supplementary material Appendix 1). A combined species network can therefore better accommodate turnover, already demonstrated as important for wintering waterbirds showing rapid distribution shifts in response to recent warming 35,36 . Alternatively, the network could focus on the sites supporting the largest populations (likely to be the biggest and best-quality sites) which, in the case of SPAs, are those which qualify on the assemblage criterion.…”
mentioning
confidence: 99%
“…Many factors have been reported to negatively affect duck species worldwide at both a site and flyway level, such as breeding and wintering habitat degradation and loss due to oil pollution, drainage, eutrophication, agricultural intensification and industrial development, hunting disturbance, lead shot poisoning and avian influenza outbreaks (del Hoyo et al 1992;Mateo et al 1998;Kear 2005;Melville and Shortridge 2006). Furthermore, in recent decades, the influence of global climate change has been implicated in the 'short stopping' of migratory bird populations where wintering conditions closer to breeding areas may have become more favourable during the winter period, thus enabling a range of species to reduce migration distance (Scott and Rose 1996;Snow and Perrins 1998;Dalby et al 2013;Lehikoinen et al 2013). Lehikoinen et al (2013) demonstrated strong northeastwards shifts in the centres of gravity of the entire wintering range of three common waterbird species, including tufted duck, along the North-West European flyway during the past three decades.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in recent decades, the influence of global climate change has been implicated in the 'short stopping' of migratory bird populations where wintering conditions closer to breeding areas may have become more favourable during the winter period, thus enabling a range of species to reduce migration distance (Scott and Rose 1996;Snow and Perrins 1998;Dalby et al 2013;Lehikoinen et al 2013). Lehikoinen et al (2013) demonstrated strong northeastwards shifts in the centres of gravity of the entire wintering range of three common waterbird species, including tufted duck, along the North-West European flyway during the past three decades. Dalby et al (2013) found that temperature clearly plays a role in shaping the winter distribution of six dabbling duck species but concluded that other factors, probably related to feeding ecology, may also influence their distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on ringing data from the Netherlands, Visser et al (2009) found that 12 of 24 species studied showed a significant reduction in their migration distance to the south, and that this was strongly correlated with the Dutch winter temperature in the year of recovery. For three common waterfowl species, Lehikoinen et al (2013) demonstrated that shifts in wintering areas to the northeast correlated with an increase of 3.8°C in early winter temperature in the north-eastern part of the wintering areas, where bird abundance increased exponentially, corresponding with decreases in abundance at the south-western margin of the wintering ranges. In line with these findings, Maclean et al (2008) showed that the centres of wintering distribution for five species of wading birds along the north-western European coast flyway shifted 95 km north-eastwards within the period 1981-2000.…”
Section: Changes In Phenologymentioning
confidence: 98%